2013
DOI: 10.1002/lary.24121
|View full text |Cite
|
Sign up to set email alerts
|

Access to the parapharyngeal space: An anatomical study comparing the endoscopic and open approaches

Abstract: 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 15 publications
(33 reference statements)
0
53
0
Order By: Relevance
“…Lesions located in the parapharyngeal space have been most commonly reported. Most are benign in nature (80%), including paragangliomas, schwannomas, small salivary gland tumors (especially pleomorphic adenomas), parotid tumors, and meningiomas with extracranial extension, which may compress or encase these structures superiorly within the parapharyngeal space. Among paragangliomas, carotid body tumors are most common (> 50%) .…”
Section: Discussionmentioning
confidence: 99%
“…Lesions located in the parapharyngeal space have been most commonly reported. Most are benign in nature (80%), including paragangliomas, schwannomas, small salivary gland tumors (especially pleomorphic adenomas), parotid tumors, and meningiomas with extracranial extension, which may compress or encase these structures superiorly within the parapharyngeal space. Among paragangliomas, carotid body tumors are most common (> 50%) .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Transoral robotic surgery (TORS) has also been developed over the past decade as a minimally-invasive transoral approach with pharyngeal and laryngeal tumors, as an alternative to open surgery, and it has become part of the standard-of-care for management of oropharyngeal and supraglottic laryngeal carcinomas. [24][25][26] The potential application of TORS for skull base surgery has been explored since the beginning, but the lack of suitable instruments for bone drilling as well as the bulkiness of the early generations of robotic systems have limited its development in clinical practice. [24][25][26] The potential application of TORS for skull base surgery has been explored since the beginning, but the lack of suitable instruments for bone drilling as well as the bulkiness of the early generations of robotic systems have limited its development in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease surgical invasiveness and improve the visual field in parapharyngeal space tumor surgery, the robot‐assisted transoral approach and endoscopic transnasal (endonasal)‐transmaxillary‐transpterygoid approach recently have been introduced. Taniguchi and Kohmura and Van Rompaey et al reported their findings on cadaver dissections used to assess the feasibility of the endoscopic transnasal‐transmaxillary‐transpterygoid approach, and Battaglia et al described their clinical findings on the use of this approach on patients. The Battaglia et al approach involved the removal of part of the nasal septum and a medial maxillectomy, which included the removal of the inferior turbinate and lateral nasal wall.…”
Section: Introductionmentioning
confidence: 99%